THE ANALYSIS OF AUTHENTICITY IN SUMMATIVE ASSESSMENT IN AVOCATIONAL SCHOOL IN BANDUNG - Fauziah Fauziah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2019)
Authenticity is one of effective testcriteria and principles that are important in language testing as it is in language teaching. The crucial aspects of task authenticity are whether real communication takes place and the language has been used for genuine purpose. Large-scale multiple-choice tests that were used as summative assessment cannot offer much authenticity, nor can portfolios and such alternatives achieve much practicality or reliability. The challenge that was faced by teachers is to transform the inauthenticity produced tests into more pedagogically fulfillment. Hence, this study focuses on analysis of authenticity in summative assessment and a number of approaches. The data collected was summative test in one of vocational school in Bandung. The analysis used five questions to evaluate the extent to which a test is authentic. The study found out that accomplishing the inauthenticity was extra job for teacher. It demanded effort in fulfilling one of important aspect in language testing. Keywords: Authenticity, Language testing, Summative assessment